Access to healthcare for people living with HIV: an analysis of judgments of the European Court of Human Rights from an ethical perspective - Skuban-Eiseler, Tobias; Orzechowski, Marcin; Steger, Florian (Frontiers in Public Health, 2023)
Introduction Although HIV has been part of our reality for over 30 years, people living with HIV (PLHIV) still experience restrictions regarding their access to healthcare. This poses a significant ethical problem, especially as it endangers achieving the goal of ending the HIV epidemic worldwide. The aim of this paper is to analyze the rulings of the European Court of Human Rights (ECtHR) regarding cases where PLHIV experienced restrictions on their access to healthcare. Methods We conducted an analysis of the ECtHR database and were able to identify N = 28 cases dealing with restricted access to healthcare for PLHIV. A descriptive and thematic analysis was conducted to identify ways in which access to healthcare for PLHIV was restricted. Results We were able to identify a total of four main categories, with denial of adequate therapeutic support as the main category with N = 22 cases (78.57%). Most of the judgments examined were filed against Russia (N = 12, 42.86%) and Ukraine (N = 9, 32.14%). A large proportion of PLHIV in the cases studied (N = 57, 85.07%) were detainees. Discussion The analysis shows a clear condemnation of limited access to healthcare for PLHIV by the ECtHR. Ethical implications of the analyzed cases are discussed in detail.